Grandparenting Children with Disabilities - Harrington Meyer, Madonna; Abdul-Malak, Ynesse; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2020)
Childhood disabilities, particularly cognitive disabilities, are on the rise yet social programs and services to help US families respond to disabilities are not. Many families turn to grandparents for assistance juggling work, family responsibilities, and specialized therapies. This book is based on in-depth interviews with grandparents who are providing at least some care to grandchildren with disabilities. The analyses will help to better understand (1) under what conditions grandparents provide care and support, (2) what types and intensities of care and support grandparents provide, and (3) the impact of that care and support on grandparents$1 (Bsocial, emotional, physical, and financial wellbeing. In this fascinating and provocative book, Madonna Harrington Meyer and Ynesse Abdul-Malak take readers on a deep dive into the complex lives of grandparents who care for their disabled grandchildren. In Grandparenting Children with Disabilities, their interviews reveal the joy, meaning, and purpose grandparents find in caregiving, the challenges and frustrations they encounter, and the many ways they compromise their own health and well-being for the sake of their grandchildren. Drawing from theories of cumulative inequality and from their deep knowledge of the US policy context, the authors lay bare the systemic failures that leave families of children with disabilities without adequate support and that place the most vulnerable among them at grave physical, emotional, and financial risk$1! = (BJane McLeod, Provost Professor, Indiana University Grandparents in the U.S. already take on far more parenting responsibilities as compared to their peers in other countries. Grandparenting Children with Disabilities demonstrates that the intensity of these responsibilities is compounded for those whose grandchildren have disabilities given limited policy supports and a society still largely unaccommodating to those with disabilities. This book beautifully navigates the tension between the love these grandparents have for their grandchildren and the challenges they face caring for them. Pamela Herd, Professor, Georgetown University Grandparenting Children with Disabilities offers important insights about the lived experience of older adults who care for and care about their grandchildren$1! =(BThe authors skillfully integrate the stories they tell with consideration of macro social structural influences and life course perspectives$1! = (BI recommend it highly! Eva Kahana, Distinguished University Professor, Case Western Reserve .s
Chapter 1 Grandparenting Children with Disabilities -- Chapter 2 Joys and Special Bonds -- Chapter 3 Intensive Grandparenting -- Chapter 4 Never-ending Grandparenting -- Chapter 5 Supporting Therapy -- Chapter 6 Juggling Grandparenting and Jobs -- Chapter 7 Redefining Social Lives -- Chapter 8 Emotional Ups and Downs -- Chapter 9 Implications for Physical Health -- Chapter 10 Financial Wellbeing -- Chapter 11 Conclusions: Policy and Programmatic Implications.
Keywords: Social groups; Family; Medical research; Quality of life; Aging; Sociology of Family, Youth and Aging; Quality of Life Research; Quality of Life Research; Aging